(3TQM MeGSI CHj JeGes - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3aEf faS heG edcJ jejfi ahGQS UObJ ajge Xfhfi s
(3BNQgG (B:s
(3hEfi dCfS YfO cd MajXg EPG bjd ehdGc GMJeGd GdVZGFf s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B119 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B692s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs